2012
DOI: 10.3109/09553002.2012.700166
|View full text |Cite
|
Sign up to set email alerts
|

Sterilization of bone allografts by microwave and gamma radiation

Abstract: The study shows that sterilization of contaminated femoral head bone allografts can be achieved by short exposure of 2 min to 2450 MHz and 900 W microwave radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Besides, microwave irradiation sterilization has been considered in this study as a successful sterilization method which sterilized materials at 3 min of irradiation at 900 W and 2450 MHz. According to another study performed by Singh [26], microwave irradiation (2450 MHz and 900 W) of contaminated bone samples showed no growth of microorganisms after 2 min of exposure. Shamis et al.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, microwave irradiation sterilization has been considered in this study as a successful sterilization method which sterilized materials at 3 min of irradiation at 900 W and 2450 MHz. According to another study performed by Singh [26], microwave irradiation (2450 MHz and 900 W) of contaminated bone samples showed no growth of microorganisms after 2 min of exposure. Shamis et al.…”
Section: Discussionmentioning
confidence: 99%
“…Dunsmuir et al [39] have reported sterilization of femoral head allograft by microwave. The process of microwave sterilization was found to be effective for sterilization of bone allografts processed from femoral heads contaminated with Gram-positive and Gram-negative bacteria [40] . Electron beam is a high energy electron treatment which is currently used for sterilization of medical devices and in radiation therapy.…”
Section: Methods For Sterilization Of Tissue Allograftsmentioning
confidence: 99%
“…Studies have identified insufficient penetration as a key limitation of alternative sterilization technologies 1 . Although some evidence indicates that microwave sterilization is effective for bone allografts 28 , evidence supporting microwave sterilization in general, and its use for other tissues is limited compared to the evidence for gamma radiation.…”
Section: Impacts – Medical – United Statesmentioning
confidence: 99%